(untitled) (Research, Society and Development, 2021)
The production of passion fruit in Brazil is mainly focused on the production of sour passion fruit, as it attracts greater interest on the part of consumers. The propagation of this species is done mainly through seeds, but it can also be carried out by vegetative propagation. The objective was to evaluate the rooting of sour passion fruit cuttings with application of IBA in different concentrations and two types of cuttings (with and without leaves). The cuttings used were collected in Uruana-GO and had two buds. A randomized block design was used in a 2 x 4 factorial arrangement (cuttings with and without leaves; four concentrations of IBA: 0, 1,000, 2,000 and 4,000 mg L-1), with five replicates and five cuttings per experimental unit. The treated cuttings were established in a sand bed, in the greenhouse. The cuttings were evaluated 40 days after planting. The variables used were the cuttings: live, dead, rooted, with calluses and number of shoots. The treatments of IBA in the lowest dose (zero) and in the highest dose (4,000 mg L-1) provided higher percentages of live cuttings, with corns and number of shoots. There was a decrease in cuttings rooting with the increase in IBA doses. The increase in IBA doses up to 2,000 mg L-1 provided higher cuttings mortality. The presence of leaves in the cuttings produced a higher percentage of live cuttings, rooted, with calluses and shoots. Leafless cuttings produced more dead cuttings. The most suitable treatment is the non-application of IBA and the use of cuttings with leaves.